IMPACT OF CORONAVIRUS ON THE RUSSIAN ECONOMY - Vera Dzhabrailovna Kuzmenkova (Наука Красноярья, 2020)
The coronavirus epidemic (COVID-19) is an insidious disease that is spreading rapidly around the world, negatively affecting the entire human community. COVID-19 affects people’s health, all areas of activity, both inside and outside the country.